Human Diseases Associated with Notch Signalling: Lessons from Drosophila melanogaster - Marvel Megaly; Anel Turgambayeva; Ryan D. Hallam; Gregory Foran; Mark Megaly; Aleksandar Necakov (Frontiers in Bioscience-Landmark, 2024)
Drosophila melanogaster has been used as a model system to identify and characterize genetic contributions to development, homeostasis, and to investigate the molecular determinants of numerous human diseases. While there exist many differences at the genetic, structural, and molecular level, many signalling components and cellular machineries are conserved between Drosophila and humans. For this reason, Drosophila can and has been used extensively to model, and study human pathologies. The extensive genetic resources available make this model system a powerful one. Over the years, the sophisticated and rapidly expanding Drosophila genetic toolkit has provided valuable novel insights into the contribution of genetic components to human diseases. The activity of Notch signalling is crucial during development and conserved across the Metazoa and has been associated with many human diseases. Here we highlight examples of mechanisms involving Notch signalling that have been elucidated from modelling human diseases in Drosophila melanogaster that include neurodegenerative diseases, congenital diseases, several cancers, and cardiac disorders.